Assessing dietary diversity in pregnant women: Relative validity of the list-based and open recall methods - Nguyen, Phuong Hong; Martin-Prevel, Yves; Moursi, Mourad; Tran, Lan Mai; Menon, Purnima; Ruel, Marie T.; Arimond, Mary (American Society for Nutrition, 2020)
Background: The Minimum Dietary Diversity for Women (MMD-W) was validated as a proxy of micronutrient adequacy for non-pregnant women, with proposed data collection being either a list-based or a qualitative open recall method. Few studies have compared the performance of these two methods. Objectives: We compared performance in predicting micronutrient adequacy of food group indicators (FGIs) measured by the list-based and the quantitative open recall method using varying quantity cutoffs. We also examined the agreement between list-based and open recall FGIs.